PENGARUH DOSIS P DALAM FOSFAT ALAM PADA PENINGKATAN BIOMASA Azolla microphylla Kaulfuss - Mahmudah Hamawi (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2015)
Azolla microphylla is one of the green resources fertilizer, adding natural P respectively will increase the biomass including. The on time embedding of azolla are able to provide nutrition to the plants such as rice especially N. The experiment was conducted in Desember 2nd , 2006 - April 5th , 2007 in Tegalgondo, Karangploso, Malang, East Java ( 550 m up sea level). The experiment applied Randomized Block Design (RBD) under two factors, dose and embedding time with three replications. The doses were applied are P0 = 0 kg ha-1; P1 = 25 kg P ha-1; P2 = 50 kg P ha-1; and P3 = 75 kg P ha-1 . The embedding times were a day before planting, 50 % azolla in 14, 28 and 24 days after planting, 50 % azolla in 21 and 49 days after planting, and 50 % azolla in 35 day after planting. The parameters of observation were wet weigh of azolla; N, P , K contents before and after treatments and azolla decompositions. The result showed 75 kg P ha-1 with interaction of azolla embedding, was the most effective dose to increased azolla biomass.